Process Analysis for Achieving Highly Enhanced Total Efficiency on Multi-Stage Fuel Supplied SOFC System. (2nd June 2015) - Tachikawa, Yuya; Matsuzaki, Yoshio; Hatae, Toru; Taniguchi, Shunsuke; Sasaki, Kazunari
Abstract : A multi-stage fuel supply SOFC system is studied, which has additional fuel supply inlets between each SOFC stack. The anode offgas from the first stack is supplied to the next stack as reformed fuel gas being mixed with additional fresh fuel. In this paper, the effect of the additional fuel flow ratio is evaluated. The electric efficiency and the fuel utilization of the system can be improved in applying multi-stage fuel supply design.